The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/jacs.0c07578
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis and Sequencing of Si–H and C–H Bond Activation Reactions: Direct Silylation of Arenes Catalyzed by an Iridium-Polyhydride

Abstract: The saturated trihydride IrH 3 {κ 3 -P,O,P-[xant(P i Pr 2 ) 2 ]} (1; xant(P i Pr 2 ) 2 = 9,9-dimethyl-4,5bis(diisopropylphosphino)xanthene) coordinates the Si-H bond of triethylsilane, 1,1,1,3,5,5,5-heptamethyltrisiloxane, and triphenylsilane to give the σ-complexes IrH 3 (η 2 -H-SiR 3 ){κ 2 -cis-P,P-[xant(P i Pr 2 ) 2 ]}, which evolve to the dihydride-silyl derivatives IrH 2 (SiR 3 ){κ 3 -P,O,P-[xant(P i Pr 2 ) 2 ]} (SiR 3 = SiEt 3 (2), SiMe(OSiMe 3 ) 2 (3), SiPh 3 (4)) by means of the oxidative addition of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 100 publications
(86 reference statements)
0
13
0
Order By: Relevance
“…Why do aryl C–H bonds react faster than benzylic C–H bonds? To the best of our knowledge, mechanistic studies on C–H silylations mainly focused on hydrosilanes and theoretical studies on SCBs focused on cycloadditions. While the collective body of knowledge about C–H silylations is undoubtedly inspirational, the answers to the above questions are not readily clear. We thus strived to decode the puzzle to further capitalize the potential of SCBs and the Rh/diphosphine catalyst system in C–H silylations.…”
Section: Introductionmentioning
confidence: 99%
“…Why do aryl C–H bonds react faster than benzylic C–H bonds? To the best of our knowledge, mechanistic studies on C–H silylations mainly focused on hydrosilanes and theoretical studies on SCBs focused on cycloadditions. While the collective body of knowledge about C–H silylations is undoubtedly inspirational, the answers to the above questions are not readily clear. We thus strived to decode the puzzle to further capitalize the potential of SCBs and the Rh/diphosphine catalyst system in C–H silylations.…”
Section: Introductionmentioning
confidence: 99%
“…20e , 22 Accordingly, diphosphine xant(P i Pr 2 ) 2 allows structural changes in its complexes, to adapt the metal coordination sphere to the needs of the reactions. As a result, a number of metal derivatives stabilized by this ligand have proven to be active catalysts for a range of interesting organic transformations, 10h , 20a , 20d , 21b , 21f − 21h , 23 including cross-coupling reactions that involve elemental steps of σ-bond activation in both substrates such as the borylation 10g , 24 and silylation 25 of arenes. As a part of the chemistry of the Rh-xant(P i Pr 2 ) 2 moiety, we have previously reported that the square-planar rhodium(I)-hydride complex RhH{κ 3 -P,O,P-[xant(P i Pr 2 ) 2 ]} activates C–H and C–Cl bonds of arenes to afford the corresponding rhodium(III) species RhH 2 (aryl){κ 3 -P,O,P-[xant(P i Pr 2 ) 2 ]} and RhH(aryl)Cl{κ 3 -P,O,P-[xant(P i Pr 2 ) 2 ]}, which eliminate H 2 and HCl, respectively, to form a wide variety of square-planar derivatives Rh(aryl){κ 3 -P,O,P-[xant(P i Pr 2 ) 2 ]}.…”
Section: Introductionmentioning
confidence: 99%
“… 3 The reason for this fact is because they are ideal for setting unsaturated organic molecules at metal fragments, 4 can generate radicals with Markovnikov selectivity by H· transfer, 5 and have demonstrated a marked ability to functionalize C–H bonds as consequence of their capacity to activate σ-bonds. 6 Thus, complexes bearing both classes of ligands have an enormous potentiality, being the stabilization and control over their chemical properties a challenge of first magnitude.…”
Section: Introductionmentioning
confidence: 99%